PARENTAL ATTACHMENT STYLE DAN CELEBRITY WORSHIP PADA PENGGEMAR ATLIT BULUTANGKIS INDONESIA - Mistety Oktaviana; Karisma Riskinanti (PSYCHOPEDIA : Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2024)
The sport of badminton in Indonesia is growing, and more and more athletes are making Indonesia proud on the international stage. Fans of badminton athletes are also in the spotlight considering the many negative comments given to other athletes who are opponents of their idols. The form of awe towards an idol is known as celebrity worship. Celebrity worship has three levels of admiration, namely social entertainment, intense personal, and borderline pathological. Individuals with a pathological borderline are usually willing to break the rules for their idol. Much literature states that celebrity worship is related to attachment style. Therefore, this research is interested in examining the relationship between parental attachment style and celebrity worship on badminton athlete fans in Indonesia. This research will be carried out with a quantitative approach with a correlational design. Cabang olahraga bulutangkis di Indonesia semakin berkembang, dan semakin banyak atlet yang mengharumkan nama Indonesia di kancah internasional. Penggemar dari para atlet bulutangkis pun menjadi sorotan mengingat banyaknya komentar negative yang diberikan kepada atlet lain yang menjadi lawan dari idolanya tersebut. Bentuk perasaan kagum terhadap sosok idola disebut sebagai celebrity worship. Celebrity worship memiliki tiga tingkatan level kekaguman, yaitu entertainment social, intense personal, dan borderline pathological. Pada individu dengan borderline pathological biasanya rela untuk melanggar peraturan demi sang idola. Banyaknya literature menyatakan bahwa celebrity worship berhubungan dengan attachment style. Oleh karena itu penelitia tertarik untuk menguji hubungan antara parental attachment style dengan celebrity worship pada penggemar atlet bulutangkis di Indonesia. Penelitian ini akan dilaksanakan dengan pendekatan kuantitatif dengan desain korelasional.